CLUSTER MISSION AND DATA ANALYSIS FOR THE MARCH 2001 MAGNETIC STORM - Frutos Alfaro F.; Korth A.; Fränz M.; Mouikis C.G.; Kistler L.M.; Möbius E.; Kucharek H.; Klecker B.; Rème H.; Dandouras I.; Bosqued J.M.; Sauvaud J.A.; et al. (My University, 2004)
The CLUSTER mission is intended for the study of the Earth’s magnetosphere and Sun-Earth relationships. Four satellites fly in a tetrahedral formation sending data that can separate spatial from temporal effects for the first time. This formation will provide a better understanding of microscopic and macroscopic features in the magnetosphere and the solar wind. As an illustration we discuss the CIS data during a large magnetic storm.
Keywords: CLUSTER mission; magnetic storm; ion spectrometry